Molecular Mechanisms Lead to Sex-Specific COVID-19 Prognosis and Targeted Therapies - Galbadage, Thushara; Peterson, Brent M.; Wang, Jeffrey S.; Jayasekara, Avishka; Ramirez, Danny A.; Awada, Joseph; Walsh, John P.; Gunasekera, Richard S. (Frontiers in Medicine, 2020)
Clinical and epidemiological studies have identified male sex as an important risk factor for COVID-19 clinical outcomes and mortality. This raises the question as to how this risk factor can be addressed in the prognosis, clinical management, and the treatment of patients with Coronavirus disease 2019 (COVID-19). Currently, there are no guidelines or protocols to help alter the course of sex-specific COVID-19 prognosis, especially in severe disease presentations. This is partly due to the lack of research studies characterizing the differences in male vs. female host response to the severe acute respiratory syndrome Coronavirus-2 (SARS-CoV-2) infection and a lack of a well-rounded understanding of the molecular mechanisms involved. Here, we discuss three distinct, but interconnected molecular-level differences in males and females that likely play an essential role in the COVID-19 prognosis. We review interactions of SARS-CoV-2 with host cell angiotensin-converting enzyme 2 (ACE2) in the viral entry between males vs. females and discuss the differential regulation of the renin-angiotensin system (RAS) between the two sexes. Next, we present immune response disparities and how immune function and endocrine regulation may render males increasingly vulnerable to severe COVID-19. We describe the interconnected roles of these three regulatory systems in males and females in response to SARS-CoV-2 infection. Finally, we highlight the clinical implications of these mechanisms to patients with COVID-19 and propose putative targeted therapies that can help reduce COVID-19 severity in those critically ill.